Irony and the other Off Record Strategies within Politeness Theory - Laura Alba Juez (Miscelánea: A Journal of English and American Studies)
The present paper is part of a more complete study of the phenomenon of verbal irony within the framework of Politeness theory as presented by Brown and Levinson in their book Politeness: Some Universals in Language Use (1987, first published 1978). The possibility of combining an off record strategy such as irony with on record strategies has already been considered (Alba Juez, 1994a). In the present paper some examples are presented which illustrate the combination of verbal irony with the other off record strategies set out in the theory by Brown and Levinson. It is taken for granted that thereader is familiar with Politeness Theory, and hence many concepts are not explained or defined herein.